Differences in meristem size and expression of branching genes are associated with variation in panicle phenotype in wild and domesticated African rice. Issue 1 (December 2017) - Ta, K.; Adam, H.; Staedler, Y.; Schönenberger, J.; Harrop, T.; Tregear, J.; Do, N.; Gantet, P.; Ghesquière, A.; Jouannic, S.
Abstract Background The African riceOryza glaberrima was domesticated from its wild relativeOryza barthii about 3000 years ago. During the domestication process, panicle complexity changed from a panicle with low complexity inO. barthii, to a highly branched panicle carrying more seeds inO. glaberrima . To understand the basis of this differential panicle development between the two species, we conducted morphological and molecular analyses of early panicle development. Results Using X-ray tomography, we analyzed the morphological basis of early developmental stages of panicle development. We uncovered evidence for a wider rachis meristem inO. glaberrima than inO. barthii . At the molecular level, spatial and temporal expression profiles of orthologs ofO. sativa genes related to meristem activity and meristem fate control were obtained using in situ hybridization and qRT-PCR. Despite highly conserved spatial expression patterns betweenO. glaberrima andO. barthii, differences in the expression levels of these early acting genes were detected. Conclusion The higher complexity of theO. glaberrima panicle compared to that of its wild relativeO. barthii is associated with a wider rachis meristem and a modification of expression of branching-related genes. Our study indicates that the expression of genes in themiR156 /miR529 /SPL andTAW1 pathways, along with that of their target genes, is altered from the unbranched stage of development. This suggests that differences in panicle complexity between the two African rice species result from early alterations to gene expression during reproductive development.